2006
DOI: 10.1291/hypres.29.731
|View full text |Cite
|
Sign up to set email alerts
|

A Miso (Japanese Soybean Paste) Diet Conferred Greater Protection against Hypertension than a Sodium Chloride Diet in Dahl Salt-Sensitive Rats

Abstract: The purpose of this study was to compare the effects of miso and sodium chloride (NaCl) on blood pressure in both sexes of Dahl and SD rats. The systolic and diastolic blood pressures (SBP/DBP) were measured at 2, 4, 8 and 12 weeks of treatment with a miso diet including 2.3% NaCl, a high-sodium diet including 2.3% or 1.9% NaCl, or a normal diet including 0.3% NaCl (MF diet; Oriental Yeast Co., Tokyo, Japan). The rats were autopsied after 12 weeks on a diet. DBP in male Dahl rats was significantly increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
(27 reference statements)
1
32
0
Order By: Relevance
“…To date, clinical studies provided evidence that small peptides have an ability to elicit antihypertensive effect in mild hypertensive subjects (Hata and others 1996; Kawasaki and others 2000). An interesting finding was also reported that 10% miso‐diet containing 2.3% NaCl significantly suppressed a promoting BP rise in salt‐sensitive Dahl rats compared with control diet containing 2.3% NaCl (Watanabe and others 2006). Although the mechanism remains unclear, it seems likely that some peptides in miso paste may be responsible for the effect via, for example, angiotensin I‐converting enzyme (ACE, EC 3.4.15.1) inhibition (Hata and others 1996), L‐type Ca 2+ channel blocker (Matsui and others 2005), or heme oxygenase‐1 activator (Erdmann and others 2006).…”
Section: Introductionmentioning
confidence: 74%
“…To date, clinical studies provided evidence that small peptides have an ability to elicit antihypertensive effect in mild hypertensive subjects (Hata and others 1996; Kawasaki and others 2000). An interesting finding was also reported that 10% miso‐diet containing 2.3% NaCl significantly suppressed a promoting BP rise in salt‐sensitive Dahl rats compared with control diet containing 2.3% NaCl (Watanabe and others 2006). Although the mechanism remains unclear, it seems likely that some peptides in miso paste may be responsible for the effect via, for example, angiotensin I‐converting enzyme (ACE, EC 3.4.15.1) inhibition (Hata and others 1996), L‐type Ca 2+ channel blocker (Matsui and others 2005), or heme oxygenase‐1 activator (Erdmann and others 2006).…”
Section: Introductionmentioning
confidence: 74%
“…As described before, unlike the cases of salt alone, the salt in miso reduced stomach cancer 72 , and miso did not cause an increase in gastric tumors. So the effects of salt in miso on blood pressure were studied 88 .…”
Section: Protection Against Hypertensionmentioning
confidence: 99%
“… Systolic blood pressure in female rats 88 . *Significantly different from same strain control (p<0.05).…”
Section: Protection Against Hypertensionmentioning
confidence: 99%
“…One of the inactivation pathways of CAs is the enzymatic metabolism by catechol-O-methyltransferase (COMT; EC2.1.1.6), which methylates their catechol moieties using S-adenosyl-L-methionine (SAMe) as a methyl donor.1) There are two COMT isoforms: in the cytoplasm as soluble COMT (S-COMT) and in association with membranes as membrane-bound COMT (MB-COMT).We have previously reported a rapid assay method for COMT activities using high-performance liquid chromatography (HPLC)-fluorescence detection.2) In this study, we applied the method to brain tissues, such as cerebral cortex, cerebellum, hypophysis and hypothalamus.In previous report using Sprague-Dawley (SD) rats, the cerebral cortex and the cerebellum were seemed to be important parts in brain for the metabolism of NE.3) Furthermore, the experiment with spontaneously hypertensive rats (SHR) suggested an association between MB-COMT in the cerebral cortex and blood pressure.4) Hence, in order to clarify the role of COMT in rat brain in relation to salt-sensitive hypertension, COMT activities in Dahl salt-sensitive (DS) rats, 5,6) which are model rats of salt-sensitive hypertension, were also examined. …”
mentioning
confidence: 99%
“…4) Hence, in order to clarify the role of COMT in rat brain in relation to salt-sensitive hypertension, COMT activities in Dahl salt-sensitive (DS) rats, 5,6) which are model rats of salt-sensitive hypertension, were also examined.…”
mentioning
confidence: 99%